Light-emitting element, display device, and method for manufacturing light-emitting element
By adding high-concentration distribution additives and inorganic semiconductors to the matrix material of the light emitting element, filling the region between quantum dots and controlling the crystal growth rate, the problem of low durability of the light emitting element is solved, and higher luminous efficiency and durability are achieved.
Patent Information
- Application Number
- CN202280098283.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-05
- Publication Date
- 2025-03-11
AI Technical Summary
The existing light emitting elements have low durability, and there are problems with fluorescence resonance energy movement (FRET) caused by a decrease in luminous efficiency and a decrease in the distance between quantum dots.
A light emitting layer containing the first quantum dot and the second quantum dot is adopted. The matrix material contains inorganic semiconductors and additives. The concentration of the additive is higher than that of other parts in the high concentration distribution area. It is used to fill the area between the quantum dots, and control the crystal growth rate and the thermal diffusion rate of the additive.
By improving the concentration distribution of the matrix material and crystal growth control, the durability and external quantum efficiency (EQE) of the light emitting element are significantly improved.
Smart Images

Figure CN119605316A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a light emitting element, a display device, and a method for manufacturing the light emitting element. Background Art
[0002] Patent Document 1 discloses quantum dots having a fluoride-containing ligand or a fluoride anion bonded to the surface. Prior art literature Patent Literature
[0003] Patent Document 1: Japanese Patent Application Laid-Open No. 2020-180278 (published on November 5, 2020) Summary of the invention Technical problem to be solved by the invention
[0004] The invention described in Patent Document 1 has a problem in that the durability of the light emitting element is low. Solutions for solving technical problems
[0005] One embodiment of the present invention relates to a light-emitting element having a light-emitting layer, wherein the light-emitting layer includes: a first quantum dot and a second quantum dot; and a matrix material, wherein the matrix material (1) contains an inorganic semiconductor and an additive, (2) is filled between the first quantum dot and the second quantum dot, and (3) has: a first part, adjacent to the first quantum dot; a second part, adjacent to the second quantum dot; and a third part, located between the first part and the second part and having a higher concentration of the additive than the first part and the second part.
[0006] In a method for manufacturing a light-emitting element according to one embodiment of the present invention, a dispersion containing a precursor of an inorganic semiconductor, an additive, a plurality of quantum dots and a solvent is applied, and the precursor of the inorganic semiconductor is modified into the inorganic semiconductor so that the crystal growth rate of the inorganic semiconductor is equal to or lower than the thermal diffusion rate of the additive. Effects of the Invention
[0007] According to one aspect of the present disclosure, the durability of a light emitting element can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] Figure 1 It is a cross-sectional view showing a configuration example of a light emitting element according to one embodiment of the present disclosure. Figure 2 It is shown Figure 1 Schematic diagram of an example of the region between quantum dots shown. Figure 3 It is shown Figure 1 A schematic diagram of another example of the region between quantum dots is shown. Figure 4 It is shown Figure 1Schematic diagram of a configuration example of the light-emitting layer shown. Figure 5 It is shown Figure 1 Schematic diagram of another configuration example of the light-emitting layer shown. Figure 6 Is focused on Figure 4 and Figure 5 Schematic diagram of a first quantum dot and a second quantum dot adjacent to each other. Figure 7 It is shown along Figure 5 The arrows BC are a diagram of an example of the concentration distribution of additives. Figure 8 yes Figure 4 A schematic diagram of an example of dispersing additives in the illustrated configuration example. Fig. 9 It is shown Figure 1 A flow chart of an example of a method for manufacturing a light emitting element is shown. Fig.10 It is shown in the formation Fig. 9 FIG. 1 is a schematic diagram showing an example of a dispersion liquid used in the step of forming the light-emitting layer. Fig.11 It is shown that the formation Fig. 9 A flowchart of an example of a process for forming a light-emitting layer is shown. Fig.12 Graphs showing light emission characteristics of a light emitting element according to an example of the present disclosure and a light emitting element according to a comparative example. Fig.13 It is a schematic diagram showing a configuration example of a light-emitting layer of a light-emitting element according to an embodiment of the present disclosure. Fig.14 It is shown Fig.13 A schematic diagram of an example of dispersing additives in the illustrated configuration example. Fig.15 Is focused on Fig.13 and Fig.14 Schematic diagram of a first quantum dot and a second quantum dot adjacent to each other. Fig.16 Schematic diagram showing a modification of the light-emitting layer of the light-emitting element according to the embodiment of the present disclosure. Fig.17 It is a schematic diagram showing a configuration example of a light emitting device according to an embodiment of the present disclosure. DETAILED DESCRIPTION
[0009] [First embodiment] (Cross-sectional structure of light-emitting element) Figure 1 1 is a cross-sectional view showing a configuration example of a light emitting element according to an embodiment of the present disclosure. Figure 1As shown, the light emitting element 10 involved in this embodiment includes a first electrode E1 and a second electrode E2 facing each other, and a light emitting layer Em located between the first electrode E1 and the second electrode E2. The light emitting element 10 may further include a charge functional layer F1 between the first electrode E1 and the light emitting layer Em, and may further include a charge functional layer F2 between the second electrode E2 and the light emitting layer Em.
[0010] At least one of the first electrode E1 and the second electrode E2 is a transparent electrode. One of the first electrode E1 and the second electrode E2 is an anode, and the other is a cathode. The charge functional layers F1 and F2 include any one or more of a charge injection layer, a charge transport layer, and a charge blocking layer. The light-emitting layer Em includes: a plurality of quantum dots QD including a first quantum dot QD1 and a second quantum dot QD2; and a matrix material Mx. The matrix material Mx (1) includes an inorganic semiconductor and an additive Ad (refer to Figure 8 ), (2) filled between the first quantum dot QD1 and the second quantum dot QD2. The additive Ad may include at least one of a halogen element and an organic compound.
[0011] The matrix material Mx refers to a component that contains and retains other substances, and can be called a substrate, a base material, or a filling material. The matrix material Mx can also be solid at room temperature. The matrix material Mx can also be a component that contains and retains the first quantum dot QD1 and the second quantum dot QD2. The matrix material Mx can also be a constituent element of the light-emitting layer Em that contains the first quantum dot QD1 and the second quantum dot QD2.
[0012] Figure 2 as well as Figure 3 They are shown respectively Figure 1 Schematic diagram of an example of the region between quantum dots shown. The matrix material Mx can also be filled in the light-emitting layer Em. Figure 1 As shown, the matrix material Mx can also fill the area (space) B between the first and second quantum dots QD1 and QD2. Figure 2 and Figure 3 As shown in the cross-sectional view, region B is a region surrounded by two straight lines (common tangent lines) connected to the peripheries of the first and second quantum dots QD1 and QD2, and the opposing peripheries of the first and second quantum dots QD1 and QD2. Figure 3 As shown, even if the first quantum dot QD1 is close to the second quantum dot QD2, region B may still exist. Figure 1 As shown, the matrix material Mx can also fill the region (space) other than the plurality of quantum dots including the first and second quantum dots QD1 and QD2 in the light-emitting layer Em. The matrix material Mx can fill the region (space) other than the quantum dot group in the light-emitting layer Em. Furthermore, the three or more quantum dots including the first and second quantum dots QD1 and QD2 are collectively referred to as a quantum dot group.
[0013] The matrix material Mx can fill the area (space) other than the multiple quantum dots including the first and second quantum dots QD1 and QD2 in the light-emitting layer Em. The outer edge (upper surface and lower surface) of the light-emitting layer Em can also be covered by the matrix material Mx. In addition, it can also be configured that a portion of the matrix material Mx exists from the outer edge of the light-emitting layer Em, and the quantum dots QD are located at a position away from the outer edge. The outer edge of the light-emitting layer Em can also be formed not only by the matrix material Mx, but also a portion of the quantum dots are exposed from the matrix material Mx. The matrix material Mx can also represent the portion other than the multiple quantum dots including the first and second quantum dots QD1 and QD2 in the light-emitting layer Em.
[0014] The matrix material Mx may contain the first and second quantum dots QD1, QD2. The matrix material Mx may contain a quantum dot group including the first and second quantum dots QD1, QD2. The matrix material Mx may also be formed to fill the space formed between the first and second quantum dots QD1, QD2. The matrix material Mx may also partially or completely fill the space between the quantum dot groups including the first and second quantum dots QD1, QD2. The light-emitting layer Em has a quantum dot group including the first and second quantum dots QD1, QD2, and the matrix material Mx may also fill the area outside the quantum dot group. The first and second quantum dots QD1, QD2 may be buried in the matrix material Mx at intervals.
[0015] The matrix material Mx may include a continuous film having a thickness of 1000 nm along a plane direction perpendicular to the thickness direction of the light emitting layer Em. 2 The continuous film refers to a film that is not interrupted on one plane by materials other than the material constituting the continuous film. The continuous film may also be an integrated film that is connected without interruption by chemical bonds of the materials constituting the matrix material Mx.
[0016] The matrix material Mx may also be the same material as the shell of the first quantum dot QD1. In this case, the average distance between adjacent cores (inter-core distance) may be greater than 3 nm, or greater than 5 nm. Alternatively, the average distance between the adjacent cores may be greater than 0.5 times the average core diameter. The inter-core distance is the distance averaged by averaging the shortest distances between 20 adjacent cores. Preferably, the inter-core distance is wider than the distance when the shell materials are in contact with each other. The average core diameter is the average value of the core diameters of 20 adjacent cores in cross-sectional observation. The core diameter may be the diameter of a circle with the same area as the core area in cross-sectional observation.
[0017] The concentration of the matrix material Mx in the light-emitting layer Em is, for example, the area ratio occupied by the matrix material Mx in the cross section of the light-emitting layer Em. In cross-sectional observation, the concentration may be greater than 10% and less than 90%, or greater than 30% and less than 70%. For example, the concentration may be determined based on the area ratio in image processing in cross-sectional observation. When the first quantum dot QD1 is a core-shell structure, the concentration of the shell may be greater than 1% and less than 50%. The shell material and the matrix material Mx are the same material (same composition), and when the shell and the matrix material Mx cannot be distinguished, the concentration of the area where the matrix material Mx and the shell are added together may be the numerical range obtained by adding the numerical range of the concentration of the shell to the numerical range of the concentration of the matrix material Mx. The ratio of the core to the shell and the matrix material Mx of the quantum dot QD may be appropriately adjusted to a total value of less than 100%. In this way, when the shell and the matrix material Mx cannot be distinguished, the shell may also be regarded as part of the matrix material Mx.
[0018] The light-emitting layer Em may also be composed of a plurality of quantum dots including the first and second quantum dots QD1 and QD2 and a matrix material Mx. When analyzing the light-emitting layer Em, the intensity of carbon detected by the chain structure may be below noise.
[0019] The band gap of the constituent material of the matrix material Mx is preferably greater than the constituent material of the first and second quantum dots QD1 and QD2. As the material constituting the matrix material Mx, a semiconductor or an insulator can be used. Examples of constituent materials of the matrix material Mx include metal sulfides and / or metal oxides. Metal sulfides may be, for example, zinc sulfide (ZnS), zinc magnesium sulfide (ZnMgS, ZnMgS2), gallium sulfide (GaS, Ga2S3), zinc tellurium sulfide (ZnTeS), magnesium sulfide (MgS), zinc gallium sulfide (ZnGa2S4), and magnesium sulfide (MgGa2S4). Metal oxides may be zinc oxide (ZnO), titanium oxide (TiO2), tin oxide (SnO2), tungsten oxide (WO3), and zirconium oxide (ZrO2). In addition, the chemical formula recorded in parentheses after the compound name is a representative example. In addition, with respect to the composition ratio recorded in the chemical formula, it is preferred if the composition of the actual compound is stoichiometric as shown in the chemical formula, but it may not necessarily be stoichiometric.
[0020] The structure of the matrix material Mx can be seen as the above structure when observed in a cross section of the light-emitting layer Em with a width of about 100 nm, and the above structure does not need to be observed in the entire light-emitting layer Em. The matrix material Mx may also contain a substance different from the main material (e.g., an inorganic substance such as an inorganic semiconductor) as an additive.
[0021] (Constitution of the Light Emitting Layer) Figure 4 and Figure 5They are shown respectively Figure 1 The schematic diagram of the composition example of the light-emitting layer shown is equivalent to Figure 1 The enlarged cross-sectional view of the part shown in the enclosed portion A is enlarged. Figure 4 and Figure 5 As shown, the matrix material Mx has a plurality of crystal portions CG including a first crystal portion CG1 and a second crystal portion CG2. The matrix material Mx may be a so-called "polycrystalline". The first crystal portion CG1 is a single crystal epitaxially grown from the surface of the first quantum dot QD1, and the second crystal portion CG2 is a single crystal epitaxially grown from the surface of the second quantum dot QD2. The configuration and orientation of the lattice G1 of the first crystal portion CG1 are in accordance with the configuration and orientation of the lattice G2 on the surface of the first quantum dot QD1. The configuration and orientation of the lattice G1 of the second crystal portion CG2 are in accordance with the configuration and orientation of the lattice G2 on the surface of the second quantum dot QD2. Furthermore, a plurality of crystal portions CG may be in contact with one quantum dot QD, and one crystal portion CG may contain more than two quantum dots QD. Below, for the sake of simplicity, unless otherwise stated, as Figure 4 and Figure 5 As shown, a configuration example in which the first crystal portion CG1 includes the first quantum dot QD1 is described.
[0022] like Figure 4 and Figure 5 As shown, between the first quantum dot QD1 and the second quantum dot QD2 adjacent to each other, the first crystal portion CG1 grown from the surface of the first quantum dot QD1 and the second crystal portion CG2 grown from the surface of the second quantum dot QD2 contact each other to form a grain boundary Bd. Figure 4 As shown in FIG. 1 , the configuration of quantum dots QD is generally random, and the crystal orientations of the outermost layers of the quantum dots QD are different from each other. Therefore, in the grain boundary Bd, the lattice G1 and the crystal orientation of the first crystal portion CG1 and the second crystal portion CG2 do not match. In addition, as Figure 5 As shown, even if the quantum dots QD are arranged neatly and the crystal orientation of the outermost layer of the quantum dots QD matches, as long as the interval between the first quantum dot QD1 and the second quantum dot QD2 is not an integer multiple of the lattice constant of the first crystal part CG1 and the second crystal part CG2, the lattice G1 of the first crystal part CG1 and the second crystal part CG2 does not match. In the grain boundary Bd of the crystal part CG, since at least one of the crystal orientation and the lattice G1 does not match, the grain boundary Bd is also called a "crystal mismatching surface."
[0023] Figure 6 Is focused on Figure 4 Schematic diagram of a first quantum dot QD1 and a second quantum dot QD2 adjacent to each other. Figure 6As shown, the matrix material Mx includes: a first portion P1 adjacent to the first quantum dot QD1, a second portion P2 adjacent to the second quantum dot QD2, and a third portion P3 located between the first portion P1 and the second portion P2. The additive Ad in the third portion P3 (refer to Figure 8 ) is higher than the concentration of the additive Ad in the first part P1 and the second part P2.
[0024] In the matrix material Mx, the third portion P3 is included to form a high concentration distribution region Hp having a higher concentration of the additive Ad than the first portion P1 and the second portion P2. The first portion P1 and the second portion P2 may contain a portion where the concentration of the additive Ad is 0. The additive Ad is dispersed in the third portion P3.
[0025] The middle position between the first quantum dot QD1 and the second quantum dot QD2 exists in the third part P3. The first quantum dot QD1 and the second quantum dot QD2 are respectively surrounded by the high concentration distribution area Hp. Figure 4 As shown, in the cross-sectional view of the light-emitting layer Em including the cross-sectional view of the first quantum dots QD1 and the second quantum dots QD2, the high-concentration distribution region Hp is in a mesh shape.
[0026] Figure 7 It is shown along Figure 5 The arrows BC are an example of the concentration distribution of additives. Figure 7 As shown, the additive Ad (refer to Figure 8 ) concentration is the largest at the grain boundary Bd, and the surface additive Ad (refer to Figure 8 ) concentration is reduced. And, using Figure 5 This concentration distribution is described, but even in other configurations (such as Figure 4 ), can also have the same concentration distribution. Furthermore, in the configuration example where a plurality of crystal parts CG are connected to the first quantum dot QD1, if a three-dimensional region is assumed to include a plurality of crystal parts CG connected to the first quantum dot QD1, the concentration of the additive Ad decreases from the boundary surface of the three-dimensional region to the surface of the first quantum dot QD1.
[0027] Therefore, the base material Mx has a plurality of crystal portions CG, and at least a portion of the grain boundary Bd in the base material Mx is included in the high concentration distribution region Hp. Figure 8 ) decreases from the boundary surface of the three-dimensional region to the surface of the first quantum dot QD1 and the second quantum dot QD2. The concentration of the additive Ad at a certain position can be calculated as the density of the additive Ad per unit volume centered at the position.
[0028] Figure 8 Yes means Figure 4Schematic diagram of the dispersion example of the additive in the composition example shown. Figure 8 As shown, the additive d is dispersed in the grain boundary Bd and its vicinity (i.e., the high concentration distribution area Hp) of the crystal portion CG. As a result, the additive Ad inactivates the lattice defects of the grain boundary Bd (and its vicinity). In the structure without the additive Ad, since the grain boundary Bd is a crystal mismatch surface, dangling bonds are generated at a high density at the grain boundary Bd (and its vicinity). The dangling bonds become non-luminescent bond centers or carrier traps, reducing the luminous efficiency of the light-emitting layer Em. On the other hand, in the structure involved in the present invention, the additive Ad accepts unpaired electrons from the dangling bonds. As a result, the dangling bonds are eliminated.
[0029] Therefore, the additive Ad contains one or more halogen elements. The one or more halogen elements may also contain any one or more of fluorine, chlorine, bromine and iodine. Preferably, the one or more halogen elements belong to the same period or a higher period as at least one of the elements constituting the matrix material Mx. In addition, when the one or more halogen elements contain two or more halogen elements, the halogen element with the largest amount ratio among the two or more halogen elements preferably belongs to the same period or a higher period as at least one of the elements constituting the matrix material Mx.
[0030] According to the characteristics such as the wavelength of the light emitted by the first quantum dot QD1, II-VI compounds, III-V compounds, perovskite compounds, chalcopyrite compounds, etc. are used on the core of the first quantum dot QD1. On the other hand, in order to enclose excitons in the core of the first quantum dot QD1, compounds with a band gap larger than that of the core material are mostly used in the shell of the first quantum dot QD1. The constituent material of the shell of the first quantum dot QD1 can be the same as the constituent material of the inorganic semiconductor contained in the matrix material Mx. The band gap of the inorganic semiconductor contained in the matrix material Mx can be larger than the band gap of the constituent material of the core of the first quantum dot QD1.
[0031] In the present disclosure, a III-V compound refers to an inorganic compound containing a III group element and a V group element in a composition ratio of about 1:1, and a II-VI compound refers to an inorganic compound containing a II group element and a VI group element in a composition ratio of about 1:1. Group II elements include Group 2 elements and Group 12 elements. Group III elements include Group 3 elements and Group 13 elements. Group IV elements include Group 4 elements and Group 14 elements. Group VI elements include Group 6 elements and Group 16 elements. Here, the notation of the genus number of an element using Roman numerals is based on the notation of the old IUPAC method or the old CAS method, and the notation of the genus number of an element using Arabic numerals is based on the notation of the new IUPAC method.
[0032] Group 6 elements are also called chalcogens. Chalcogens include oxygen, sulfur, selenium, and tellurium. Group 2 elements and Group 12 elements are all metal elements. Therefore, Group II-VI compounds containing Group 6 elements are also called metal chalcogenides. Metal chalcogenides refer to any one of the crystal types of wurtzite, sphalerite, and rock salt. In metal chalcogenides, defects in which chalcogens are missing are easily generated. The ease with which a halogen element bonds to this defect has nothing to do with the crystal type and depends on the ionic radius. The closer the ionic radius of a halogen element is to the ionic radius of a chalcogen element, the easier it is to bond. When the ionic radius of a halogen element is less than or equal to the ionic radius of a chalcogen element, it is easier to bond than when the ionic radius of a halogen element is greater than the ionic radius of a chalcogen element.
[0033] Therefore, when the matrix material Mx includes a metal chalcogenide, it is preferred that the one or more halogen elements belong to the same period or a higher period as at least one of the chalcogen elements constituting the metal chalcogenide of the matrix material Mx. In addition, when the one or more halogen elements include two or more halogen elements, the halogen element with the largest amount ratio among the two or more halogen elements preferably belongs to the same period or a higher period as at least one of the chalcogen elements constituting the metal chalcogenide. The matrix material Mx may contain a metal sulfide.
[0034] It is known that the ionic radius of the elements belonging to the second period of the long periodic table and the ionic radius of the elements belonging to the third period and later are significantly different due to the difference in electrostatic shielding of the atomic nucleus caused by the closed shell. Therefore, when the matrix material Mx contains a chalcogen element of the second period (i.e., oxygen), the additive Ad also preferably contains a halogen element of the second period (i.e., fluorine). When the matrix material Mx contains a chalcogen element of the third period and later, it is preferred that the additive Ad also contains a halogen element of the third period and later.
[0035] In the high concentration distribution region Hp (including the third portion P3) of the matrix material Mx, the concentration of the additive Ad may be equal to the density of the dangling bonds in the entire matrix material Mx. Specifically, the concentration of the additive Ad in the third portion P3 may be 10 16 / cm 3 above 10 19 / cm 3 The following range.
[0036] And / or, the additive Ad may contain one or more organic compounds. In this case, the additive Ad accepts unpaired electrons from the dangling bond, or has both the dangling bond and the electron, thereby eliminating the dangling bond. The organic compound may be a ligand. The carbon chain of the organic compound is a short chain. In the present invention, "short chain" means that the number of carbon atoms is 6 or less.
[0037] In the present invention, "organic" refers to the so-called "organic compound". The covalent bond is cut and the organic compound is decomposed by electric current, heat, light, water and oxygen. Patent document 1 discloses a quantum dot having a fluoride-containing ligand or a fluoride anion bonded to the surface, and the fluoride-containing ligand or the fluoride anion is an organic compound. When the organic compound bonded to the surface deteriorates, the distance between the quantum dots becomes smaller, and it becomes easy to transfer fluorescence resonance energy (FRET). Or / and, the quantum dots agglomerate or deactivate. As a result, the luminous efficiency decreases. Therefore, in the prior art disclosed in patent document 1, there is a problem of low durability of the light-emitting element.
[0038] On the other hand, "inorganic" refers to so-called "inorganic compounds". Inorganic compounds are not easy to decompose compared to organic compounds. The base material Mx involved in the present disclosure is composed of inorganic semiconductors and is therefore difficult to decompose. Therefore, the method of the present disclosure can improve the durability of the light-emitting element. Here, it is to be noted that the inorganic semiconductor constituting the base material Mx may contain impurities. For example, the base material Mx may also contain residues and decomposition products of organic compounds such as organic solvents, organic surfactants, organic ligands and organic photoresists. The third part P3 of the base material Mx may contain carbon element.
[0039] The inorganic semiconductor contained in the matrix material Mx can be a monomer composed of one type of Group 14 element, for example, diamond (C), silicon (Si), or germanium (Ge). The inorganic semiconductor can be a compound composed of two or more Group 14 elements, for example, SiC or GeC. The inorganic semiconductor contained in the matrix material Mx can be an inorganic compound composed of two or more elements in Group I elements, Group II elements, Group III elements, Group IV elements, Group V elements, Group VI elements, and Group VII elements, and a mixed crystal thereof. The inorganic semiconductor can be, for example, a Group II-VI compound such as MgO, MgS, ZnO, ZnS, ZnSe, and ZnTe, and a mixed crystal thereof. The inorganic semiconductor can be, for example, a Group III-V compound such as BN, AlN, GaN, InN, AlP, GaP, InP, AlAs, GaAs, and InAs, and a mixed crystal thereof. The inorganic semiconductor can be, for example, an oxide such as Al2O3, Ga2O3, In2O3, and SiO2. The inorganic semiconductor can be, for example, a nitride such as SnN. The inorganic semiconductor may be a compound composed of one or more transition metal elements and one or more Group 6 elements other than oxygen. The transition metal elements include Group 3 to Group 12 elements, and the Group 6 elements other than oxygen include sulfur (S), selenium (Se), and tellurium (Te). The inorganic semiconductor contained in the matrix material Mx may be a ternary compound such as a perovskite compound and a chalcopyrite compound, or a compound composed of four or more elements.
[0040] The organic ligand agent contained as the additive Ad is an organic compound capable of bonding to the surface of the first quantum dot QD1. In particular, it is preferably an organic compound capable of bonding to a specific site such as a defect. Examples of organic ligand agents include TOP (trioctylphosphine), TOPO (trioctylphosphine oxide), oleic acid, oleylamine, octylamine, trioctylamine, hexadecylamine, octanethiol, dodecanethiol, hexylphosphonic acid (HPA), tetradecylphosphonic acid (TDPA), octylphosphinic acid (OPA), and the like.
[0041] The matrix material Mx may include (excluding the cross section of the quantum dot QD) 1000 nm in the plane direction (xy plane direction) orthogonal to the layer thickness direction (z direction) of the light-emitting layer Em. 2 A continuous film over an area of ??1.
[0042] (Manufacturing method) Fig. 9 Yes means Figure 1 A flowchart of an example of a method for manufacturing a light-emitting element is shown. Fig. 9 As shown, first, prepare a substrate (step S1). The substrate can be a simple supporting substrate or an active substrate with wiring and circuit elements formed on the supporting substrate. Next, form a first electrode E1 on the substrate (step S2), form a charge functional layer F1 (step S3), and form a light-emitting layer Em (step S4).
[0043] Fig.10 It is shown in the formation Fig. 9 Schematic diagram of an example of a dispersion liquid used in the process of the light-emitting layer shown in FIG. Fig.10 As shown, the dispersion L1 contains an inorganic semiconductor precursor My, an additive Ad, a plurality of quantum dots QD, and a solvent L2. When the inorganic semiconductor constituting the matrix material Mx is a metal sulfide, the precursor My may contain, for example, a metal acetate, a metal nitrate or a metal halide as a metal source, and at least one of thiourea, N-methylthiourea, 1,3-dimethylthiourea, N,N'-dimethylthiourea, tetramethylthiourea or thioacetamide as a sulfur source. Alternatively, the precursor 36 may contain a metal complex of thiourea, N-methylthiourea, 1,3-dimethylthiourea, N,N'-dimethylthiourea, tetramethylthiourea, or thioacetamide coordinated on a metal atom. The additive Ad acts as a ligand agent to protect the quantum dots QD. Therefore, at least a portion of the additive Ad is coordinated to the surface of the quantum dots QD.
[0044] Fig.11 It is shown that the formation Fig. 9 A flowchart of an example of the process of forming a light-emitting layer is shown. Fig.11As shown, in the step of forming the light-emitting layer (step S4), first, the dispersion liquid L1 is applied on the charge functional layer F1 (step S11). Then, the applied dispersion liquid L1 is dried (step S12). In the drying, the dispersion liquid L1 is heated at a temperature lower than the decomposition temperature of the precursor My to volatilize the solvent L2.
[0045] Then, the dried dispersion L1 is solidified. (Step S102). In the solidification, the dispersion L1 is heated at a high temperature higher than the decomposition temperature of the precursor My to decompose the precursor My to form an inorganic semiconductor. Any one or more of the heating time, the heat preservation time, and the cooling time in the high-temperature heating is set to delay the crystal growth of the inorganic semiconductor. Thus, instead of high-temperature heating to modify the precursor My of the inorganic semiconductor into an inorganic semiconductor, or on this basis, visible light or near-ultraviolet light is irradiated on the dried dispersion L1, so that the crystal growth rate of the crystal part CG of the inorganic semiconductor epitaxially grown from the surface of the quantum dot QD is equal to or less than the thermal diffusion rate of the additive Ad, thereby decomposing the precursor My.
[0046] Such slow crystal growth separates and concentrates the additive Ad between the growing crystal parts CG. The result of separation and concentration is shown in FIG. As described above, a high concentration distribution region Hp is formed. Therefore, the additive Ad is easily bonded to the lattice defects of the grain boundary Bd (and its vicinity).
[0047] Refer again Fig. 9 After forming the light-emitting layer (step S4), the charge functional layer F2 is formed (step S5), and the second electrode E2 is formed (step S6). Furthermore, in order to protect the light-emitting element 10 from water and oxygen, a thin film sealing layer covering the light-emitting element 10 may also be formed.
[0048] (Examples and Comparative Examples) Fig.12 It is a graph showing the light emission characteristics of the light emitting element of the example of the present disclosure and the light emitting element of the comparative example. Fig.12 The horizontal axis represents the current density applied to the light-emitting elements 10 and 20, and the vertical axis represents the external quantum efficiency (EQE) of the light-emitting elements 10 and 20. Fig.12 As shown, the current density at which the EQE peaks in the light-emitting element 10 of the embodiment of the present invention is smaller than the current density at which the EQE peaks in the light-emitting element 20 of the comparative example. In addition, the peak value of EQE in the light-emitting element 10 of the embodiment of the present disclosure is greater than the peak value of EQE in the light-emitting element 20 of the comparative example.
[0049] As mentioned above Figures 9 to 11As described above, the light-emitting element 10 of the embodiment involved in the present disclosure was manufactured. Therefore, the crystal growth of the crystal part CG contained in the matrix material Mx in the light-emitting element 10 of the embodiment is slow. On the other hand, the light-emitting element 20 of the comparative example is manufactured in a manner that the crystal growth is fast in step S13, and in other respects, it is manufactured in the same manner as the light-emitting element 10 of the embodiment. In addition, the materials used in the light-emitting element 10 of the embodiment are the same as the materials used in the light-emitting element 20 of the comparative example.
[0050] In the light-emitting element 20 of the comparative example, it is inferred that the additive Ad is not bonded to the lattice defects generated at high density at the grain boundary Bd (and its vicinity). Therefore, the dangling bonds in the lattice defects act as non-luminescent bonding centers or carrier traps, the carrier injection efficiency to the quantum dots QD is reduced, and the probability of luminescent rebonding is reduced. As a result, the EQE of the light-emitting element 20 shows a peak on the high current density side, and the peak value is as low as about 5%.
[0051] On the other hand, in the light-emitting element 10 of the embodiment, it is inferred that the additive Ad is bonded to the lattice defects generated at a high density at the grain boundary Bd (and in the vicinity thereof). Therefore, the lattice defects are deactivated. As a result, compared with the light-emitting element 20 of the comparative example, the EQE of the light-emitting element 20 of the embodiment shows a peak on the low current density side, and the peak value is improved to about 15%.
[0052] [Second embodiment] Other embodiments of the present disclosure will be described below. In addition, for the sake of convenience, components having the same functions as those described in the above embodiments are denoted by the same reference numerals, and their description will not be repeated.
[0053] Fig.13 Schematic diagram showing a configuration example of a light-emitting layer of a light-emitting element according to an embodiment of the present disclosure. Fig.13 As shown, in the light-emitting layer Em of this embodiment, the first crystal portion CG1 and the second crystal portion CG2 are separated from each other to form a grain boundary Bd. The portion between the first crystal portion CG and the second crystal portion CG2 of the matrix material Mx can be polycrystalline or amorphous, preferably amorphous. In other respects, the structure of the light-emitting element 10 of this embodiment is the same as the structure of the light-emitting element 10 of the first embodiment described above.
[0054] Fig.14 Yes means Fig.13 Schematic diagram of the dispersion example of the additive in the composition example shown. Fig.14As shown, the additive Ad is dispersed in the grain boundary Bd of the crystal portion CG and its vicinity (i.e., the high concentration distribution region Hp). Therefore, according to the configuration of this embodiment, the durability and EQE of the light-emitting element 10 are improved as in the configuration of the first embodiment described above. In addition, the EQE of the light-emitting element 10 shows a peak at a low current density.
[0055] Fig.15 Is focused on Fig.13 and Fig.14 Schematic diagram of a first quantum dot QD1 and a second quantum dot adjacent to each other. Fig.15 As shown, the matrix material Mx has a first portion P1, a second portion P2, and a third portion P3, and further has a fourth portion P4 located between the second portion P2 and the third portion P3, and a fifth portion P5 located between the third portion P3 and the fourth portion P4. The concentration of the additive Ad in the fourth portion P4 is higher than the concentration of the additive Ad in the first portion P1 and the second portion P2. The concentration of the additive Ad in the fifth portion P5 is lower than the concentration of the additive Ad in the third portion P3 and the fourth portion P4.
[0056] Separately formed in the matrix material Mx are: a high concentration distribution area Hp in which the concentration of the additive Ad is higher than that of the first part P1 and the second part P2 and includes the third part P3; and a high concentration distribution area Hp in which the concentration of the additive Ad is higher than that of the first part P1 and the second part P2 and includes the fourth part P4. The fifth part P5 is not included in the high concentration distribution area Hp. The first part P1, the second part P2, and the fifth part P5 may contain a portion in which the concentration of the additive Ad is 0. The additive Ad is dispersed in the third part P3 and the fourth part P4. The first quantum dot DQ1 is surrounded by the high concentration distribution area Hp including the third part P3, and the second quantum dot QD2 is surrounded by the high concentration distribution area Hp including the fourth part P4.
[0057] The shape of the crystal portion CG and the configuration of the high concentration distribution area Hp depend on the shape of the quantum dot QD and the crystal growth rate. For example, a portion of the high concentration distribution area Hp is along a roughly spherical surface centered on the first quantum dot QD1. For example, the interval between a portion of the high concentration distribution area Hp and the surface of the first quantum dot QD1 is constant.
[0058] (Variation Example) Fig.16 Schematic diagram showing a modification of the light-emitting layer of the light-emitting element according to one embodiment of the present disclosure. Fig.16As shown, the light-emitting layer Em of the light-emitting element 10 may also have an intermediate structure between the structure involved in the first embodiment and the structure involved in the second embodiment. For example, a part of adjacent crystal parts CG may be in contact with each other. For example, a plurality of adjacent crystal parts CG may be separated from each other, and another plurality of adjacent crystal parts CG may be in contact with each other.
[0059] [Third embodiment] Other embodiments of the present disclosure will be described below.
[0060] Fig.17 Schematic diagram showing a configuration example of a display device according to an embodiment of the present disclosure. Fig.17 As shown, a display device 30 according to one embodiment of the present disclosure includes one or more light emitting elements 10 according to the present disclosure. The display device 30 includes a self-luminous display device and a display device using the light emitting element 10 as a backlight.
[0061] The present disclosure is not limited to the above-mentioned embodiments, and various changes can be made within the scope of the claims. The embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included in the technical scope of the present disclosure. Moreover, new technical features can be formed by combining the technical methods disclosed in each embodiment. DESCRIPTION OF REFERENCE NUMERALS
[0062] 10 Light-emitting elements 30 Display device Ad Additives Bd Grain Boundary Em Emissive Layer Hp high concentration distribution area L1 Dispersion L2 Solvent Mx Base material My Precursor P1 Part 1 P2 Part 2 P3 Part 3 P4 Part 4 P5 Part 5 QD Quantum Dots QD1 The first quantum dot QD2 Second Quantum Dot
Claims
1. A light-emitting element having a light-emitting layer, characterized in that: The light-emitting layer comprises: A first quantum dot and a second quantum dot; and A matrix material, wherein the matrix material (1) contains an inorganic semiconductor and an additive, (2) is filled between the first quantum dot and the second quantum dot, and (3) has: a first part, adjacent to the first quantum dot; a second part, adjacent to the second quantum dot; and a third part, located between the first part and the second part and having a higher concentration of the additive than the first part and the second part.
2. The light emitting element according to claim 1, wherein The light-emitting layer has a quantum dot group, and the quantum dot group includes the first quantum dot and the second quantum dot. The matrix material is filled in the area outside the quantum dot group.
3. The light emitting element according to claim 1 or 2, characterized in that: The additive contains a halogen element.
4. The light emitting element according to claim 3, wherein: The halogen element is dispersed in the third portion.
5. The light emitting element according to any one of claims 1 to 4, characterized in that The intermediate position between the first quantum dot and the second quantum dot exists in the third portion.
6. The light emitting element according to any one of claims 1 to 5, wherein On the base material, a high concentration distribution region in which the concentration of the additive is higher than that of the first portion and the second portion is formed in a manner including the third portion.
7. The light emitting element according to claim 6, wherein: The first quantum dots are surrounded by the high concentration distribution area.
8. The light-emitting element according to claim 6 or 7, characterized in that: In the cross-sectional view of the light-emitting layer, the high-concentration distribution region is in a mesh shape.
9. The light-emitting element according to any one of claims 1 to 5, characterized in that The base material has a fourth portion, the fourth portion is located between the second portion and the third portion, and the concentration of the additive is higher than that of the first portion and the second portion.
10. The light emitting element according to claim 9, wherein The base material has a fifth portion, the fifth portion is located between the third portion and the fourth portion, and the concentration of the additive is lower than that of the third portion and the fourth portion.
11. The light emitting element according to claim 9 or 10, characterized in that: Separately formed on the base material are: The concentration of the additive is higher than that of the first part and the second part, and includes a high concentration distribution area of the third part; and The concentration of the additive is higher than that of the first portion and the second portion, and includes a high-concentration distribution region of the fourth portion.
12. The light emitting element according to claim 11, wherein The first quantum dots are surrounded by the high-concentration distribution region including the third portion, and the second quantum dots are surrounded by the high-concentration distribution region including the fourth portion.
13. The light emitting element according to any one of claims 6 to 8 and 11 to 12, characterized in that The base material has a plurality of crystal parts, At least a portion of the grain boundary of the matrix material is included in the high-concentration distribution region.
14. The light emitting element according to any one of claims 6 to 8 and 11 to 13, characterized in that A portion of the high-concentration distribution region is along a substantially spherical surface centered on the first quantum dot.
15. The light emitting element according to any one of claims 6 to 8 and 11 to 14, characterized in that The interval between a portion of the high concentration distribution region and the surface of the first quantum dots is constant.
16. The light emitting element according to any one of claims 1 to 13, wherein: The first portion of the matrix material is in contact with a core or a shell of the first quantum dot.
17. The light emitting element according to claim 15, wherein: The constituent material of the shell of the first quantum dot is the same as the constituent material of the inorganic semiconductor.
18. The light emitting element according to any one of claims 1 to 17, wherein The band gap of the inorganic semiconductor is larger than the band gap of the constituent material of the core of the first quantum dot.
19. The light emitting element according to claim 3, wherein: The concentration of the halogen element in the third part is 10 16 / cm 3 above 10 19 / cm 3 the following.
20. The light emitting element according to any one of claims 1 to 19, wherein: The additive contains an organic compound.
21. The light emitting element according to claim 20, wherein: The organic compound is a ligand agent.
22. The light-emitting element according to claim 20 or 21, characterized in that: The third part contains carbon element.
23. The light emitting element according to any one of claims 20 to 22, characterized in that: The carbon chain of the organic compound is a short chain.
24. The light emitting element according to claim 3, wherein: The halogen element includes any one of fluorine, chlorine, bromine and iodine.
25. The light emitting element according to claim 3, wherein The halogen element belongs to the same period or a super-period as at least one of the elements constituting the inorganic semiconductor.
26. The light emitting element according to claim 3, wherein: The additive contains two or more halogen elements, The halogen element having the largest mass ratio among the two or more halogen elements belongs to the same period or a higher period as at least one element constituting the inorganic semiconductor.
27. The light emitting element according to claim 3, wherein: The inorganic semiconductor includes a metal chalcogenide.
28. The light emitting element according to claim 27, wherein: The halogen element belongs to the same period or a superordinate period as at least one of the chalcogen elements constituting the metal chalcogenide.
29. The light emitting element according to claim 27, characterized in that The additive contains two or more halogen elements, The halogen element having the largest mass ratio among the two or more halogen elements belongs to the same period or a higher period as at least one chalcogen element constituting the metal chalcogenide.
30. The light emitting element according to any one of claims 1 to 29, wherein: The inorganic semiconductor includes a metal sulfide.
31. The light-emitting element according to any one of claims 1 to 30, characterized in that The matrix material contains a 1000 nm area in a plane direction perpendicular to the thickness direction of the light-emitting layer. 2 Continuous film above.
32. A display device comprising the light-emitting element according to any one of claims 1 to 31.
33. A method for manufacturing a light emitting element, characterized in that: Applying a dispersion containing an inorganic semiconductor precursor, an additive, a plurality of quantum dots and a solvent, The precursor of the inorganic semiconductor is modified into the inorganic semiconductor so that the crystal growth rate of the inorganic semiconductor is equal to or lower than the thermal diffusion rate of the additive.
Citation Information
Patent Citations
Nanostructures with inorganic ligands for electroluminescent devices
JP2020180278A